1995
DOI: 10.1080/07399339509516182
|View full text |Cite
|
Sign up to set email alerts
|

Women and somatization: Unrecognized depression

Abstract: Depression is the mental health disorder most commonly seen in the primary health care setting. Estimates of the prevalence of people who are depressed but are seeking treatment for physical disorders in the primary care setting range from 12% to 55% of total patients. We conducted a study to determine the number of women with high depressive symptoms who were seeking treatment for physical disorders and compared this group with women with no depressive symptoms who were also seeking physical health care. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…Consistent with reports from primary care [24,25] , unexplained somatic symptoms were more common in women. In a psychiatric sample, Wenzel et al [47] recently concluded that the higher prevalence of self-reported somatic symptoms in women, measured by the Beck Depression Inventory II, can be largely attributed to changes in appetite.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with reports from primary care [24,25] , unexplained somatic symptoms were more common in women. In a psychiatric sample, Wenzel et al [47] recently concluded that the higher prevalence of self-reported somatic symptoms in women, measured by the Beck Depression Inventory II, can be largely attributed to changes in appetite.…”
Section: Discussionsupporting
confidence: 81%
“…Somatic symptoms are more frequently reported by women [24,25] , elderly patients, children, patients at a low social and cultural level or with coexisting physical illness and certain cultural groups [26,27] . The presence of somatic symptoms seems to be correlated with an increased use of health care services [28][29][30][31] , poor treatment compliance and chronic course of the illness [28] .…”
Section: Introductionmentioning
confidence: 99%
“…The "typical" depression presentation in primary care is dominated by physical (somatic) complaints as opposed to psychological complaints. More than 50% of patients with depression report somatic complaints only 11,12,24,[89][90][91][92] and at least 60% of these somatic complaints are pain related. 24,25,36,93 Thus, patients with depression in primary care settings are more likely to report various pain symptoms than they are to present with dysphoric mood or anhedonia.…”
Section: Does the Presence Of Pain Affect Provider Recognition And Trmentioning
confidence: 99%
“…The psychological literature tells us that anger is usually in fact an expression of fear or a response to a perceived threat. 68 Based on longitudinal studies of adjustment to SCI we know that there is signi®cant ongoing psychological adjustment and that psychological distress does not diminish signi®cantly over time. 77 Rather than reacting defensively in response to the women's anger, health care, rehabilitation and related professionals need understand that the women's anger and frustration often originates from fear.…”
Section: Discussionmentioning
confidence: 99%